2017
DOI: 10.31223/osf.io/dxs4p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A linear dynamical systems approach to streamflow reconstruction reveals history of regime shifts in northern Thailand

Abstract: Key points• The state variable reveals regime-like behavior in the catchment history• The linear dynamic model has higher accuracy than conventional linear regression • The model can generate stochastic replicates of both streamflow and catchment state time series ABSTRACT Catchment dynamics is not often modeled in streamflow reconstruction studies; yet, the streamflow generation process depends on both catchment state and climatic inputs. To explicitly account for this interaction, we contribute a linear dyna… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…D'Arrigo et al () reconstructed Indonesia's Citarum River based on ring width measurements from regional teak sites that exhibited a strong direct correlation between rainfall and September–November streamflow. More recently, Nguyen and Galelli () used the tree ring width‐derived Monsoon Asia Drought Atlas data (Cook et al, ) to reconstruct the annual flow of north Thailand's Ping River. In comparison, our simple linear regression using the CPRB18O as a predictor resulted in a reconstruction model that accounted for 57% of the variation in CPRPF for the period 1956–1999.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…D'Arrigo et al () reconstructed Indonesia's Citarum River based on ring width measurements from regional teak sites that exhibited a strong direct correlation between rainfall and September–November streamflow. More recently, Nguyen and Galelli () used the tree ring width‐derived Monsoon Asia Drought Atlas data (Cook et al, ) to reconstruct the annual flow of north Thailand's Ping River. In comparison, our simple linear regression using the CPRB18O as a predictor resulted in a reconstruction model that accounted for 57% of the variation in CPRPF for the period 1956–1999.…”
Section: Resultsmentioning
confidence: 99%
“…One promising way to extend the instrumental record of streamflow is to utilize regional tree ring records as proxies for streamflow through the connection to hydroclimate (e.g., Stockton & Jacoby, ). Due to their annual resolution, tree rings are easily comparable with observed streamflow data and have been successfully applied in many regions of the world for reconstructing streamflow (e.g., D'Arrigo et al, ; Derose et al, ; Gou et al, ; Lara et al, ; Meko et al, ; Nguyen & Galelli, ; Woodhouse et al, ). Despite the challenges associated with cross‐dating tropical tree rings, a growing body of annually dated tree ring records have emerged from Southeast Asia that make it possible to attempt such a reconstruction for the CPR.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there may be nonlinearities in the streamflow–proxy relationships at the extremes. In future studies, nonlinear reconstruction models (e.g., Nguyen & Galelli, 2018; Torbenson & Stagge, 2021) could be incorporated to address this problem.…”
Section: Resultsmentioning
confidence: 99%
“…Nguyen and Galelli () used a linear dynamic systems modeling approach to streamflow reconstruction in northern Thailand. Ho et al () demonstrated another modeling approach that was applied to reconstructing streamflow in the Missouri River Basin using a gridded paleo‐proxy called the Living Blended Drought Atlas (LBDA).…”
Section: Previous Streamflow Reconstruction Efforts and The State Of mentioning
confidence: 99%